Lo Ungeziefer della «Verwandlung» di Kafka nel processo di una nichilistica liberazione dallo Spießertum familiare. Alcune riflessioni [The Ungeziefer of Kafka’s «Verwandlung» in the process of a nihilistic release from the philistinism of the family. Some considerations] - Erminio Morenghi (Studia austriaca, 2019)
This paper problematizes the etymology of the word “Ungeziefer” in Franz Kafka’s Verwandlung, connecting it to the Jewish tradition and Egyptian mythology as well as to the anti-Semitism that flourished from the Renaissance to the early twentieth century in the German and Central European area. Gregor Samsa’s desire for freedom and emancipation embodies a monstrous and tragical metamorphosis, which gives the opportunity to free the protagonist, albeit in a humiliating and nihilistic way, from the yoke of philistinism in the family, paradoxically freeing also his relatives from a stagnant existential condition. Kafka’s “Ungeziefer” thus becomes a symbol of growth, transformation and rebirth.